Creative and educational spaces: The musician in higher education - Bennett, Dawn (International Society for Music Education, 2010)
Conservatoires and universities are both creative and educational spaces. As major employers of musicians, negotiating the nexus of teaching-research-creative practice within higher education is a critical concern for music faculty and students. This paper takes as its subject the newly introduced Excellence in Research for Australia (ERA), drawing on the experience of other research frameworks to identify some of the pertinent issues facing musicians in academia. The paper suggests that whilst creative practice is increasingly recognized as research, it is rarely judged as being research in its own right or as having equal status to traditional scientific research. Findings strengthen the argument that conceptualizing and communicating the research inherent within creative practice can give musicians both artistic and intellectual agency over the commentary that surrounds their work. However, successfully negotiating the translation of creative work into a language understood by the academy requires skills that are often far removed from creative practice. Added to increasing pressure to producetraditional written research within a narrow band of highly ranked journals, the findings suggest the need to develop a range of academic writing skills and conceptual approaches early in the training of graduate students and for new faculty. For musicians to find a balance between the creative and educational spaces of higher education, the paper presents a case for individualized support accompanied by a systemic shift that acknowledges the value, new forms of knowledge and innovative approaches within creative practice and research. The articulation of creative processes to a broad audience may prove to be a major step towards gaining this acknowledgement.